RELATIONSHIPS BETWEEN SEA SURFACE TEMPERATURE, LARGE-SCALE ATMOSPHERIC CIRCULATION, AND CONVECTION OVER THE TROPICAL INDIAN AND PACIFIC OCEANS - Orbita Roswintiarti (Pusat Penelitian dan Pengembangan BMKG, 2008)
In this paper, the quantitative estimates of the effect of large-scale circulations on the sea surface temperature (SST)-tropical convection relationship and the effect of SST on the large-scale circulation-convection relationship over the tropical Indian and Pacific Oceans are presented. Although convection tends to maximize at warm SSTs, increased deep convection is also determined by the divergence (DIV) associated with large-scale circulation. An analysis of the relationship between SST and deep convection shows that under subsidence and clear conditions, there is a decrease in convection or increase in Outgoing Longwave Radiation (OLR) at a maximum rate of 3.4 Wm-2 °C-1. In the SST range of 25°C to 29.5°C, a large increase in deep convection (decrease in OLR) occurs in the tropical Indian and Pacific Oceans. The OLR reduction is found to be a strong function of the large-scale circulation in the Indian and western Pacific Oceans. Under a weak large-scale circulation, the rate of OLR reduction is about -3.5 Wm-2 °C-1 to -8.1 Wm-2 °C-1. Under the influence of strong rising motions, the rate can increase to about -12.5 Wm-2 °C-1 for the same SST range. The overall relationship between large-scale circulation and deep convection is nearly linear. A maximum rate of OLR reduction with respect to DIV is -6.1 Wm-2 (10-6 s-1) in the western Pacific Ocean. It is also found that the DIV-OLR relationship is less dependent on SST. For example, the rate of OLR reduction over the western Pacific Ocean for 26°C < SST £ 27°C is -4.2 Wm-2 (10-6 s-1), while that for 28°C < SST £ 29°C is -5.1 Wm-2 (10-6 s-1). These results are expected to have a great importance for climate feedback mechanisms associated with clouds and SST and for climate predictability.